2013
DOI: 10.1074/mcp.m112.021238
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Genetic Analyses Demonstrate that Plasmodium berghei Blood Stages Export a Large and Diverse Repertoire of Proteins

Abstract: Malaria parasites actively remodel the infected red blood cell (irbc) by exporting proteins into the host cell cytoplasm. The human parasite Plasmodium falciparum exports particularly large numbers of proteins, including proteins that establish a vesicular network allowing the trafficking of proteins onto the surface of irbcs that are responsible for tissue sequestration. Like P. falciparum, the rodent parasite P. berghei ANKA sequesters via irbc interactions with the host receptor CD36. We have applied proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
103
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 78 publications
(165 reference statements)
9
103
2
Order By: Relevance
“…The signature PEXEL/VTS motif is strictly conserved among different malaria parasite species. In addition, a growing list of PEXEL/VTS-negative exported proteins (PNEP) is being recognized in P. falciparum and other malaria parasite species (9,10). A corresponding Plasmodium translocon of exported proteins (PTEX) (11) is present in all mammalian Plasmodium parasites.…”
mentioning
confidence: 99%
“…The signature PEXEL/VTS motif is strictly conserved among different malaria parasite species. In addition, a growing list of PEXEL/VTS-negative exported proteins (PNEP) is being recognized in P. falciparum and other malaria parasite species (9,10). A corresponding Plasmodium translocon of exported proteins (PTEX) (11) is present in all mammalian Plasmodium parasites.…”
mentioning
confidence: 99%
“…The extracellular region of var2CSA is fused to the exported protein EMAP1 (erythrocyte membrane-associated protein 1) of P. berghei that is localized at the surface membrane of P. berghei IEs (19). We found that PM pathology is more severe in mice infected with P. berghei-VAR than in mice infected with wild-type P. berghei.…”
mentioning
confidence: 67%
“…A transgenic 1037cl1 strain that expresses C-terminally var2csa-tagged EMAP1 (gene model PBANKA_0836800; emap1::var2csa; line 1653cl3) was generated as previously reported for C-terminally mCherry-tagged EMAP1 (19). The synthetic 3D7-DBL1X-6ε gene (var2csa; PF3D7_1200600) (20) was first subcloned into PCR2.1 Topo (Invitrogen, Netherlands), and the C-terminal region of emap1 from pL1534 (BamHI/SpeI) was N-terminally fused to the 3D7-DBL1X-6ε gene (NdeI/SpeI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the full scope of proteins exported across the PVM is unknown. Proteins utilizing the Plasmodium exported element (PEXEL) and PEXEL negative exported proteins (PNEP) have been identified [41][42][43]. Exported proteins are trafficked to the Maurer's clefts in the erythrocyte cytoplasm in P. falciparum infected erythrocytes.…”
Section: Bioinformatic Analysis Of Pf3d7_1436300mentioning
confidence: 99%